2001
DOI: 10.1159/000046711
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Concentration of Carotenoids, Vitamin A, Alpha-Tocopherol and Total Lipids in Human Milk throughout Early Lactation

Abstract: Background: In mammals the composition of milk changes during early lactation showing a rapid decline in fat-soluble vitamins and a continuous increase in total lipids. Changes in the concentrations of carotenoids, vitamin A, α-tocopherol and total lipids in human milk (colostrum, transitory and mature milk) were studied to understand this not well characterised phenomenon. Methods: Colostrum, transitory and mature milk was collected from 21 women and analysed for carotenoids, vitamin A and α-tocopherol by HPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
106
6
18

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(170 citation statements)
references
References 17 publications
40
106
6
18
Order By: Relevance
“…Median lutein and zeaxanthin concentrations in human milk found in this study (4.79 and 0.55 nmol/g fat, respectively) compare well with those of Macias and Schweigert (2001), who report concentrations of 3.41 mg/g (5.29 nmol/g) fat and 0.47 mg/g (0.73 nmol/g) fat for lutein and zeaxanthin, respectively. They found that concentrations of all components investigated (lutein, zeaxanthin, bcryptoxanthin, lycopene, a-and b-carotene, and retinol) decreased over time with highest values in colostrum and lowest in mature milk.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Median lutein and zeaxanthin concentrations in human milk found in this study (4.79 and 0.55 nmol/g fat, respectively) compare well with those of Macias and Schweigert (2001), who report concentrations of 3.41 mg/g (5.29 nmol/g) fat and 0.47 mg/g (0.73 nmol/g) fat for lutein and zeaxanthin, respectively. They found that concentrations of all components investigated (lutein, zeaxanthin, bcryptoxanthin, lycopene, a-and b-carotene, and retinol) decreased over time with highest values in colostrum and lowest in mature milk.…”
Section: Discussionsupporting
confidence: 87%
“…Breast milk concentrations of lutein and zeaxanthin appear to differ greatly between individuals, as is also seen in plasma (Thurnham & Northrop-Clewes, 1999). Jackson et al (1998) and Macias and Schweigert (2001) also reported a high between-subject variation in his study of milk carotenoid concentrations. The coefficient of between-subject variation in the combined lutein and zeaxanthin concentrations reported was 68% by Jackson et al (1998), and was approximately the same as found in the Irish samples (CV 68% for lutein and 72% for zeaxanthin).…”
Section: Discussionmentioning
confidence: 85%
“…15 There was no deficiency of vitamin A in the breastmilk according to parameters established by the WHO. When retinol concentrations were expressed in terms of volume of milk, a large variation was observed between collection times, although the concentrations in pooled samples were closer to vitamin A levels described in literature 15 ( Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Variation of the total fat content of the milk of the study group OG during the lactating period was similar to those found by other studies 36,37 , showing that fat content decreases over time, possibly because of a reduction in the maternal fat reserves 24 . However, the total fat contents were with in the ranges found in the literature for mature milk 38 .…”
Section: Discussionmentioning
confidence: 63%